Analysis of vortex shedding in a various body shapes - Mohd Noor, Nazihah (2015)
The study of various bluff body shapes is important in order to identify the suitable shape of bluff body that can be used for vortex flow meter applications. Numerical simulations of bluff body shapes such as circular, rectangular and equilateral triangular have been carried out to understand the phenomenon of vortex shedding. The simulation applied